Synthesis and Physicochemical Characterisation of Pristine Metal-Organic Frameworks, Thin-Films and Derived Materials - O'Doherty, Mariah (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2022)
Metal-organic frameworks (MOFs) are hybrid coordination materials, characterised by their high surface area and internal porosity, formed from organic linkers and inorganic nodes. Additionally, MOFs have the ability to act as self-sacrificing templates after thermal treatment, retaining their porosity. These methods can be used to improve the electrocatalytic water oxidation activity of a MOF. We aim to use highly-augmented MOFs for catalytic applications. Herein, an overview will be given on the synthesis and catalytic activity of a number of monometallic and mixed-metal MOFs using an augmented trifunctional benzoate ligands. These MOFs are electrochemically-synthesised on a series of thin films, giving rise to catalytic activity for the water oxidation reaction at pH 7. Bulk electrolysis experiments are conducted, confirming the long-term stability. To further improve the activity, these MOFs are annealed to produce metal oxide clusters contained within a porous carbon framework to improve stability under harsh conditions at pH 13.5 and extended stability to bulk electrolysis.
APPROVED
Keywords: metal-organic framework